Antiarthritic potential of the butanol fraction of Sesuvium sesuvioides: An in vitro, in vivo, and in silico evaluation - Muhammad Sajid-; Saiqa Ishtiaq; Hanan Y. Aati; Asmaa E. Sherif; Asmaa E. Sherif; Mohsin Abbas Khan; Mussadique Hussain; Muhammad Sohaib Khan; Maqsood Ahmed; Muhammad Jawad Naseem; Kashif- (Frontiers Media S.A., 2023)
Sesuvium sesuvioides (Fenzl) Verdc (Aizoaceae) has been traditionally used in the treatment of inflammation, arthritis, and gout. However, its antiarthritic potential has not been evaluated scientifically. The current study was designed to assess the antiarthritic properties of the n-butanol fraction of S. sesuvioides (SsBu) by phytochemical analysis, in vitro and in vivo pharmacological activities, and in silico studies. Phytochemical analysis showed total phenolic contents (90.7 ± 3.02 mg GAE/g) and total flavonoid contents (23.7 ± 0.69 mg RE/g), and further analysis by GC-MS identified possible bioactive phytocompounds belonging to phenols, flavonoids, steroids, and fatty acids. The in vitro antioxidant potential of SsBu was assessed by DPPH (175.5 ± 7.35 mg TE/g), ABTS (391.6 ± 17.1 mg TE/g), FRAP (418.2 ± 10.8 mg TE/g), CUPRAC (884.8 ± 7.97 mg TE/g), phosphomolybdenum (5.7 ± 0.33 mmol TE/g), and metal chelating activity (9.04 ± 0.58 mg EDTAE/g). Moreover, in the in vitro studies, inhibition (%) of egg albumin and bovine serum albumin denaturation assays showed that the anti-inflammatory effect of SsBu at the dose of 800 μg/ml was comparable to that of diclofenac sodium used as a standard drug. The in vivo antiarthritic activity was assessed to determine the curative impact of SsBu against formalin-induced (dose-dependent significant (p < 0.05) effect 72.2% inhibition at 750 mg/kg compared to standard; 69.1% inhibition) and complete Freund's adjuvant-induced arthritis (40.8%; inhibition compared to standard, 42.3%). SsBu significantly controlled PGE-2 level compared to the control group (p < 0.001) and restored the hematological parameters in rheumatoid arthritis. Treatment with SsBu significantly reduced oxidative stress by reinstating superoxide dismutase, GSH, and malondialdehyde along with pro-inflammatory markers (IL-6 and TNF-α) in arthritic rats. Molecular docking revealed the antiarthritic role of major identified compounds. Kaempferol-3-rutinoside was found to be more potent for COX-1 (−9.2 kcal/mol) and COX-2 inhibition (−9.9 kcal/mol) than diclofenac sodium (COX-1, −8.0 and COX-2, −6.5 kcal/mol). Out of the 12 docked compounds, two for COX-1 and seven for COX-2 inhibition showed more potent binding than the standard drug. The results from the in vitro, in vivo, and in silico approaches finally concluded that the n-butanol fraction of S. sesuvioides had antioxidant and antiarthritic potential, which may be due to the presence of potential bioactive compounds.